Assessment of Human Visual Acuity Using Visual Evoked Potential: A Review - Xiaowei Zheng; Guanghua Xu; Kai Zhang; Renghao Liang; Wenqiang Yan; Peiyuan Tian; Yaguang Jia; Sicong Zhang; Chenghang Du (Sensors, 2020)
Visual evoked potential (VEP) has been used as an alternative method to assess visual acuity objectively, especially in non-verbal infants and adults with low intellectual abilities or malingering. By sweeping the spatial frequency of visual stimuli and recording the corresponding VEP, VEP acuity can be defined by analyzing electroencephalography (EEG) signals. This paper presents a review on the VEP-based visual acuity assessment technique, including a brief overview of the technique, the effects of the parameters of visual stimuli, and signal acquisition and analysis of the VEP acuity test, and a summary of the current clinical applications of the technique. Finally, we discuss the current problems in this research domain and potential future work, which may enable this technique to be used more widely and quickly, deepening the VEP and even electrophysiology research on the detection and diagnosis of visual function.